A composite with SiOx nanoparticles confined in carbon framework as an anode material for lithium ion battery. Issue 47 (25th April 2016) - Sun, Zixu; Wang, Xinghui; Cai, Tingwei; Meng, Zhen; Han, Wei-Qiang
Abstract : A composite with ultrafine SiO x ( x = 1.57, around 2 nm) nanoparticles confined in a carbon framework is synthesized by a simple thermopolymerization process and subsequent heat treatment. Abstract : A composite with ultrafine SiO x ( x = 1.57, around 2 nm) nanoparticles confined in a carbon framework is synthesized by a simple thermopolymerization process and subsequent heat treatment. In the composite, the carbon framework can provide a consecutive network to improve the electrical conductivity of the composite and cushion the volume expansion to prevent the active material peeling from the current collector. The ultrafine SiO x nanoparticles can alleviate mechanical strain and shorten the diffusion/transport distance of lithium ions and electrons. In consequence, the as-synthesized composite delivers a high reversible capacity of 540 mA h g −1 at a current density of 500 mA g −1 after 200 cycles. The composite delivers good electrochemical performance, making it a promising candidate for the next-generation high-energy LIBs.